Asymptomatic Ileal Neuroendocrine “Carcinoid” Tumor Incidentally Diagnosed on Colorectal Cancer Screening Colonoscopy: Does Routine TI Intubation Matter? - Ali Zakaria; Lynna Alnimer; Gregory Byrd; Marc Piper; Michael Raphael; Bradley Warren; Michael Piper (Case Reports in Gastrointestinal Medicine)
Gastrointestinal neuroendocrine tumors (GINETs) (also known as “carcinoids”) are rare tumors with reported incidence of up to 6.98 per 100,000 which has increased significantly due to the increased detection on imaging and endoscopy. They are most commonly located in the small bowel, particularly the terminal ileum. Patients with small bowel NETs may present with abdominal pain, diarrhea, or carcinoid syndrome. However, the disease is mostly asymptomatic, and patients are usually diagnosed incidentally during routine colonoscopy. Although the ileum is the most common site for GINETs, terminal ileal (TI) intubation is not always completed during routine colonoscopy. With terminal ileum intubation being successful in at least 70% of colonoscopies and the rate of neuroendocrine tumor detection 0.1–1% of those intubations, one critical question remains unanswered: should terminal ileal intubation be considered a part of the definition of a complete colonoscopy? Herein, we present nine cases of NETs found incidentally on routine colon cancer screening colonoscopy in asymptomatic patients. This case series adds to the sparse literature and highlights the importance of TI intubation technique in early detection of small bowel NETs which could potentially affect the outcome.